معالجة المادة المعجمية عند ابن الأنباري: دراسة في كتابه "زينة الفضلاء" - المسيني، محمد رشاد عبدالسلام (جامعة الأزهر - كلية اللغة العربية بإيتاي البارود, 2021)
لا شك أن القدماء كانوا أحرص الناس على جمع اللغة حفاظا على الهوية العربية من براثن الاختلاط بالأمم الأخرى، ولعل ما يدل على نبل هدفهم أسماء مؤلفاتهم؛ فهي على تنوعها واختلافها تدور في فلك الحفاظ على اللغة، ولا يخفى على دارس مدقق فضل اللغويين العرب وجهودهم في العمل المعجمي، ومطالعة كتبهم لخير شاهد على حسن صنيعهم فيه، وفي هذه الدراسة التي بين أيدينا أعرض لإحدى الجهود المبذولة في معالجة المادة المعجمية سواء على مستوى المبنى أم على مستوى المعنى، فوقع اختياري على كتاب (زينة الفضلاء) لابن الأنباري (ت: 577ه) مادة للدراسة من منطلق عناية ابن الأنباري بالمعنى المعجمي. مشكلة البحث تتمثل في تحديد وسائل ابن الأنباري في معالجة البنية المعجمية من خلال الحديث عن الضبط اللغوي للكلمة من الناحية النطقية والناحية الصرفية، والكشف عن منهجه في معالجة المعنى المعجمي من خلال تتبع الأسلوب الذي سلكه في شرح المعنى، والوسائل التي اتكأ عليها في توضيح دلالة الألفاظ مع بيان دور هذه الوسائل في التفسير الدلالي باعتبار كتابه زينة الفضلاء أنموذجا للمعجمية العربية في أحد مدارسها، مستعينا بآراء وأقوال اللغويين في ذلك. وقد انتهى البحث إلى بعض النتائج أهمها ما يلي: - برزت عناية ابن الأنباري بالضبط المعجمي في تنوع الوسائل التي استخدمها لضمان سلامة الألفاظ من التحريف والتصحيف؛ حيث استخدم الضبط بالقلم، والضبط بالنص، والضبط بالوزن أو المثال. - استفاد ابن الأنباري من معطيات النظام الصوتي والصرفي والنحوي في تفسير المعنى الدلالي. - تعددت الطرق الشارحة للمعنى عند ابن الأنباري ما بين الشرح بالتعريف، والشرح بالسياق، والشرح بالتوارد أو المصاحبة، والشرح بالنظير.
There is no doubt that the ancients were the keenest to collect the language in order to preserve the Arab identity from the conflation with other nations, perhaps what indicates the nobility of their goal is the names of their writings. Despite its diversity and difference, it revolves around the sphere of preserving the language. It is no secret to a scrutinizing researcher the merits of Arab linguists and their efforts in the lexicographical work, and reading their books is the best evidence of their good deeds in it. Consequently, the current study aims to present and explore one of the efforts made in dealing with the lexical items, whether at the level of the structure or at the level of meaning. Therefore, the researcher selects Ibn al-Anbari’s book (Zina Al-Fadhla'a -577 AH) as the corpus of the study based on the attention of Ibn al-Anbari in the lexical meaning. The problem of the research is to determine the methods of Ibn al-Anbari in dealing with the structure lexical unit through exploring the linguistic regulation of the word in terms of both the phonemic and the morphological aspects. Additionally, the research aims at revealing Ibn al Anbari’s approach in dealing with the lexical meaning through tracing the method he employed in explaining the meaning, and the methods he relied upon in clarifying the semantic meaning of the words. Furthermore, the study provides an explanation of the role of these methods in semantic interpretation, considering Ibn al-Anbari’s book Zina Al- Fudhlā’ as a model for the Arabic lexicography in one of its schools, using the opinions and sayings of linguists in that. The research concluded to some results, the most important of which are the following: - Ibn Al-Anbari's concern with the lexicographical regulation was evident in the diversity of the methods that he used to ensure the integrity of words against distortion and misrepresentation. Ibn al Anbari used lexico-diacritic regulation, regulation via text/context, regulation via pattern (Wazn) or example. - Ibn Al-Anbari benefited from the data of the phonemic, morphological and grammatical system in the interpretation of the semantic meaning. - There are many ways of explaining the meaning according to Ibn Al-Anbari, between explanation by definition, explanation by context, explanation by co-occurrence or collocation, and explanation by counterpart.
Keywords: الضبط اللغوى -- التفسير الدلالي -- علم اللغة